Ilícito e pena : modelos opostos de fundamentação do direito penal contemporâneo - Scalcon, Raquel Lima (2012)
The aim of this paper is to analyze models of contemporary Criminal Law foundations which are based on the idea of unlawful (Unrecht) or the idea of criminal sanction. In this context, it aims at investigating in which core must reside its foundations. Moreover, the research hypothesizes that the theories issued from unlawful are granted a retrospective foundation, while the theories issued from criminal sanction are granted a prospective foundation. These last theories would be not consistent because consequentialist and, this way, incompatible with the concept of foundation scaffolded in this research, aimed at the past or the present. In order to develop this study, a distinction among the concepts of meaning, foundation, function and structure of Criminal Law is established. Subsequently, a brief historical evolution from its foundations in the diverse theories of the delict (causal, neoclassic and final) to actual proposals is elaborated. Then, the study examines two specific theories on Criminal Law foundation, one issued from criminal sanction (the Claus Roxin`s functionalism) and another issued from unlawful (the onto-anthropological conception from José Francisco de Faria Costa). In this process, the following theorical problems are faced: consequentialism, crime concept instrumentalization, boundaries between Criminal Law and Criminal Policies, qualitative distinction of criminal unlawfulness and other unlawfulnesses and definition of criminal legal interest and offensivity. Finally, this research proposes the foundation and the function of Criminal Law, concluding that its meaning must reside in the idea of criminal unlawful (Unrecht); its foundation, in the offense of relevant criminal legal interests, and its function, in the subsidiary protection of relevant criminal legal interests. Key